Properties, best management practices and conservation of terraced soils in Southern Europe (from Mediterranean areas to the Alps): A review - Stanchi, S.; Freppaz, M.; Agnelli, A.; Reinsch, T.; Zanini, E. (Quaternary international, 2012)
Terrace soils are distinctive features of the agricultural landscape in Europe. Due to their historical and aesthetic significance, they are a resource for agriculture and tourism: however they are also a challenge for land conservation and management. Nevertheless, the fundamental role of terrace soils for agricultural quality and natural hazard prevention has not been fully investigated. In the past, terraced slopes became ideal sites for human settlement and agricultural activities. At present, they are often used for high quality crops that grow on soils with specific chemical and physical properties. The filling material used for building terraces is a human-reworked substrate, where pedogenesis occurs under a strong human influence. This leads to soils with a generally limited pedogenic development and coarse texture, although, often, with good productivity. When abandoned, terraces are subjected to progressive decay due to erosion processes and slope failures. This review focuses on terrace soil properties, conservation and management in Southern Europe. In particular, it reports some examples from the northwestern Italian Alps, where terraced slopes are characterised by ancient origin and, presently, are subjected to specific practices for their preservation. The different effects of land degradation at hill slope scale may be mitigated through appropriate management practices favoring the terrace walls maintenance, drainage optimization, and the presence of a spontaneous vegetation cover. These subjects require careful planning and conservation measures that could be collected in “best practices” guidelines for farmers, landowners and decision-makers.